Encyclopaedia of mathematical physics Vol.II : mathematical coordinations & variations - Singh Mapal (Anmol publications, New Delhi, 2006)
Physics
ENGLISH
Keywords: Encyclopaedia of mathematical physics Vol.II : mathematical coordinations & variations; Physics; Physics